All her friends call her Alaska: the cultural politics of locating Olvido Gara in and beyond Madrid's Movida*. (1st October 2016) - Wheeler, Duncan
ABSTRACT: First coming to prominence as the bassist of one of the earliest Spanish punk bands, Kaka de Luxe, Alaska became the public face of the Movida through a starring role in Pedro Almodóvar's debut feature, Pepi, Luci, Bom y otras chicas del montón (1980), and a string of major hits as lead singer of Alaska y los Pegamoides and, subsequently, Alaska y Dinarama. The latter dissolved in 1989 when she and Nacho Canut, a constant presence and songwriter in all of her groups, formed Fangoria, a formation she has fronted to the current day. Especially following the success of MTV reality show, Alaska y Mario (2011–), the star has been heavily criticized for associating with reactionary figures, while simultaneously being variously celebrated and denigrated as a privileged icon of the Culture of the Transition. The commonplace of the two Spains as applied to the Movida has less to do with the political left and right than with a division between those who see politics everywhere, and those whom refuse to see them anywhere. This article will suggest that, while Alaska's (a)political stance is not unproblematic, commentators who reduce everything to ideology have been ill-equipped to critique the achievements and limitations of a cultural phenomenon that sought to reify aesthetics at the expense of all other considerations, politics included.